2021
DOI: 10.3390/act10060108
|View full text |Cite
|
Sign up to set email alerts
|

Active Loading Control Design for a Wearable Exoskeleton with a Bowden Cable for Transmission

Abstract: Exoskeletons with a Bowden cable for power transmission have the advantages of a concentrated mass and flexible movement. However, their integrated motor is disturbed by the Bowden cable’s friction, which limits the performance of the force loading response. In this paper, we solve this problem by designing an outer-loop feedforward-feedback proportion-differentiation controller based on an inner loop disturbance observer. Firstly, the inner loop’s dynamic performance is equivalent to the designed nominal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Through experiments in previous studies, we have verified that the parameter perturbation of the inner loop and the poor anti-interference ability can deteriorate the dynamic performance of the outer loop [ 31 ]. Furthermore, it is concluded that the inner loop based on the DOB can improve the dynamic performance potential of the outer loop.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through experiments in previous studies, we have verified that the parameter perturbation of the inner loop and the poor anti-interference ability can deteriorate the dynamic performance of the outer loop [ 31 ]. Furthermore, it is concluded that the inner loop based on the DOB can improve the dynamic performance potential of the outer loop.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the power supply, controller, and servo motor are integrated near the center of body weight. The fixation mechanism of the knee joint [ 31 ] is shown in Figure 1 , which is driven by a servo motor through a Bowden cable. Two lightweight carbon fiber boards (LCFB) and hinge mechanisms can realize rotation in the sagittal and coronal planes.…”
Section: Mathematical Modeling Of the Hesymentioning
confidence: 99%
See 2 more Smart Citations
“…[1], [2]), in the latest years there is a tendency towards a hardware simplification and a task-specific design of exoskeletons, e.g. [3]- [6], Ekso Vest (Ekso Bionics, Richmond, CA, USA), LegX and suitX (US Bionics, Inc., Emeryville, CA, USA). In parallel, several control paradigms have been studied to improve the usability of these machines and cope with the limited sensing and actuation capabilities imposed by the hardware simplification.…”
Section: Introductionmentioning
confidence: 99%